TYPHOID FEVER AND VIRAL HEPATITIS IN A G6PD DEFICIENT INDIVIDUAL - Ahmad, Imran; Ashraf, H. Muhammad; Ashraf, Shahzad (Journal of Ayub Medical College Abbottabad, 2005)
Simultaneous occurrence of multiple diseases is unusual but not rare. We are reporting an unusual combination of Typhoid fever and viral hepatitis in a G6PD deficient individual. KEY WORDS: Typhoid fever, Viral Hepatitis, G6PD Deficient